ANALISIS PENERAPAN MODEL PEMBELAJARAN DEBATE PADA MATA KULIAH BUDAYA MASYARAKAT DEMOKRATIS DALAM MENINGKATKAN KEMAMPUAN BERFIKIR KRITIS MAHASISWA PGSD - Yuli Mulyawati; Fitri Anjaswuri (Universitas Pakuan, 2020)
ANALYSIS OF THE APPLICATION OF DEBATE LEARNING MODEL IN DEMOCRATIC CULTURAL CULTURE COURSES IN ENHANCING THE CRITICAL THINKING ABILITY. PGSD STUDENTS.This research is a qualitative descriptive study based on the results of research conducted by researchers that the application of parliamentary debate learning models can improve critical thinking skills, which is the ability that everyone has to analyze ideas or ideas in a more specific direction to pursue relevant knowledge about the world by involving evaluation of evidence. The ability to think critically is needed to analyze a problem to the stage of finding a solution to solve the problem, the possibility of other answers based on analysis and information that has been obtained from a problem. Observer gives an average value of 74, 8 with very good criteria, observer 2 gives a value of 75.0 with very good criteria, observer 3 gives a value of 75.2 with very good criteria. observer gives an average value of 82.35 with very good criteria, observer 2 gives a value of 82.55 with very good criteria, observer 3 gives a value of 82.25 with very good criteria. So it can be synthesized that the Application of Debate Learning Model in the Democratic Cultural Culture course can improve the Critical Thinking Ability. PGSD students.